Isamu Noguchi. Sculptural Design - von Vegesack, Alexander; Posch, Katarina V. (Weil am Rhein : Vitra Design Museum, 2001)
catalogus die hoort bij de gelijknamige rondreizende tentoonstelling; met index; citaat website Vitra Museum:Isamu Noguchi (1904-1988) is widely considered among the most important sculptors and designers of his day. His definition of sculpture was a broad one, and he created not only sculptures, but also designed stage sets, luminaries, furniture and public spaces, effectively bridging the gap between fine arts and the applied arts. The richly illustrated catalog features among others articles on Noguchi's interiors and furniture, his relationship to Brancusi, his affiliations with the New York art world, the artist's landscape designs, as well as Japanese and American influences in Noguchi's work.
Engels
Isamu Noguchi. Sculptural Design.
boek
Keywords: Noguchi, Isamu; Brancusi, Constantin; 1922 - 1988; Verenigde Staten van Amerika; Japan